The teaching of surgery in the undergraduate curriculum--reforms and results. - Agha, R; Papanikitas, A; Baum, M; Benjamin, I (2004)
In the past decade, the teaching of surgery in the undergraduate curriculum has undergone considerable changes in quantity, mode and method of delivery. This is a result of the radical reforms of higher education, the health service and the undergraduate medical curriculum. These reforms are often interrelated and are occurring in conjunction with major changes in healthcare delivery. In this article we discuss this reorganisation, the rationale behind it and the impact on surgical teaching.